Strategi Fundraising ZISWAF melalui Teknologi Digital di Yayasan Nur Rosyidah Magetan - Sherly Marno Rahayu; Miftahul Huda; Iza Hanifuddin (Institut Agama Islam Negeri Ponorogo, 2024)
The funding institution at the Nur Rosyidah Foundation is a ZISWAF institution under the auspices of the Nur Rosyidah Magetan Foundation, which always innovates to continue to improve the quality of its services and fund collection by utilizing digital technology as a way to collect funds from donors. This research aims to determine the strategy for raising funds using digital technology, the advantages and disadvantages of raising funds, and the implications of using digital technology at the Nur Rosyidah Foundation—field research with a qualitative research approach. Meanwhile, the data collection techniques used are interview, observation, and documentation techniques. This research shows that the pattern applied at the Nur Rosyidah Foundation funding institution is an indirect fundraising method that focuses on five crowdfunding methods: paid advertising, unpaid advertising, videos and flyers, WhatsApp, and direct email. The implications of raising funds using digital technology at the Nur Rosyidah Foundation have a positive impact because the increase influences the number of funds and donors, which increases every early. The use of digital technology also has very good implications, both for internal and external circles, because the system makes it easier for consumers to donate.